Perilaku Konsumtif Mahasiswa Dalam Membeli Produk Fashion Syariah: Studi Kasus Mahasiswi FEBI UINSU - Windi Jihan Nabila; Nurbaiti Nurbaiti; Muhammad Ikhsan Harahap (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Consumptive behavior in buying fashion products for students of the Department of Islamic Economics, State Islamic University of North Sumatra. The informants of this research are students of the Department of Islamic Economics, 2018-2022, who like to shop. included in the category of consumptive behavior. The method of taking is using questionnaires or interviews. All subjects show consumptive behavior when they see good fashion products in front of their eyes. This consumptive behavior occurs initiated by factors that influence the subject's shopping style, namely environmental factors, internal factors, and fashion developments. Subjects buy not because of needs but desires, and subjects tend to often make purchases suddenly. The subject does not think about whether the items at home or at the boarding house still function, are easily tempted or interested in fashion products that other people use, cannot control themselves, and buy because they want to follow the trend. The subject of buying the product is not the priority. This unconscious behavior makes the subject tend to be consumptive in shopping. The impact or effect felt by the subject is wasteful. It is said to be wasteful because the subject spends money to buy something that is not prioritized. Keywords: Consumptive Behavior, Fashion Products